MENINGKATKAN KETERAMPILAN MENULIS CERPEN MELALUI PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE SQUARE (TPSS) PADA SISWA KELAS IX G MTSN 2 TANAH LAUT - Saudah Yani; Sujiarto Sujiarto (ADIBA : JOURNAL OF EDUCATION, 2022)
The purpose of this study was to improve poetry writing skills through Think Pair Share Square (TPSS) cooperative learning for class IX G MTsN 2 Tanah Laut students. This research was conducted for one semester. The method used is classroom action research which consists of two cycles and each cycle consists of two meetings. Each cycle consists of planning, implementing action and reflection. The results of this study indicate an increase in students' understanding of class IX G MTsN 2 Tanah Laut on the subject of poetry writing skills using a think pair share square type cooperative model. Student learning outcomes in the first cycle of learning activities averaged 69.8 with a classical completeness of 54.4% and increased to an average of 82.3 in the second cycle with 94.2% classical completeness. Student activity during learning activities increased from 53.6% in the first cycle to an average of 81.5% in the second cycle with good categories. Teacher activity has increased from an average of 3.4 with a very good category in the first cycle to an average of 3.7 with a very good category in the second cycle and there are positive student responses to the implementation of the think pair share square type cooperative model.